2021
DOI: 10.3390/galaxies9030048
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Rogue Waves in Earth’s Ionosphere

Abstract: The modulational instability of ion-acoustic waves (IAWs) in a four-component magneto-plasma system consisting of positive–negative ions fluids and non-Maxwellian (r,q) distributed electrons and positrons, is investigated. The basic system of fluid equations is reduced to a three-dimensional (3D) nonlinear Schrödinger Equation (NLS). The domains of the IAWs stability are determined and are found to be strongly affected by electrons and positrons spectral parameters r and q and temperature ratio Tp/Te (Tp and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The damped solitary excitations has been studied in multicomponent plasma [30] where the nonextensive particles effectively modify the wave amplitude. Similarly, El-Taibany have reported that the q-distributed electrons in ionospheric plasma ensue modulational instability [31], evolving highly energetic freak waves. Apart from this, many researchers have comprehended the impact of nonextensive particulate on wave dynamics in diverse plasma compositions [32][33][34].…”
Section: Introductionmentioning
confidence: 87%
“…The damped solitary excitations has been studied in multicomponent plasma [30] where the nonextensive particles effectively modify the wave amplitude. Similarly, El-Taibany have reported that the q-distributed electrons in ionospheric plasma ensue modulational instability [31], evolving highly energetic freak waves. Apart from this, many researchers have comprehended the impact of nonextensive particulate on wave dynamics in diverse plasma compositions [32][33][34].…”
Section: Introductionmentioning
confidence: 87%